Pulse-amplitude equalization using a polarization-maintaining laser resonator - Jhon, Young Min; Byun, Young Tae; Woo, Deok Ha (OPTICAL SOC AMER, 2006)
For the first time to our knowledge, pulse-amplitude equalization of rational-harmonically mode-locked fiber ring laser pulses has been experimentally demonstrated using a polarization-maintaining laser resonator without any additional device. The pulse-amplitude distribution of the laser pulses was controlled by the modulator driving power, and stable pulse-amplitude-equalized pulses with repetition rates of 20, 30, and 40 GHz have been obtained in the linear region of the modulator. (c) 2006 Optical Society of America.
Keywords: FIBER; GENERATION